Machine learning-based real-time object locator/evaluator for cryo-EM data collection - Koji Yonekura (Nature Portfolio, 2021)
Yonekura et al. present yoneoLocr, a machine learning-based real-time object locator for rapidly and precisely locating carbon holes and crystals for facilitating automated SPA or cryo-EX data collection.